Retinal Protection and Distribution of Curcumin in Vitro and in Vivo - Platania, Chiara B. M.; Fidilio, Annamaria; Lazzara, Francesca; Piazza, Cateno; Geraci, Federica; Giurdanella, Giovanni; Leggio, Gian Marco; Salomone, Salvatore; Drago, Filippo; Bucolo, Claudio (Frontiers in Pharmacology, 2018)
Diabetic retinopathy (DR), a secondary complication of diabetes, is a leading cause of irreversible blindness accounting for 5% of world blindness cases in working age. Oxidative stress and inflammation are considered causes of DR. Curcumin, a product with anti-oxidant and anti-inflammatory properties, is currently proposed as oral supplementation therapy for retinal degenerative diseases, including DR. In this study we predicted the pharmacological profile of curcumin through an in silico approach. Furthermore, we tested the anti-oxidant and anti-inflammatory activity of curcumin in human retinal pigmented epithelial cells exposed to oxidative stress, human retinal endothelial and human retinal pericytes cultured with high glucose. Because currently marketed curcumin nutraceutical products have not been so far evaluated for their ocular bioavailability; we assessed retinal distribution of curcumin, following oral administration, in rabbit eye. Curcumin (10 µM) decreased significantly (p<0.01) ROS concentration and TNF-α release in retinal pigmented epithelial cells and retinal endothelial cells, respectively. The same curcumin concentration significantly (p<0.01) protected retinal pericytes from high glucose damage as assessed by cell viability and LDH release. Among the tested formulations, only that containing a hydrophilic carrier provided therapeutic levels of curcumin in rabbit retina. In conclusion, our data suggest that curcumin, when properly formulated, may be of value in clinical practice to manage retinal diseases.